Menelisik Determinan Invisible Barriers terhadap Pengembangan Karir Perempuan Pink Collar Jobs yang Dimediasi oleh Womens Skill Development dan Dimoderasi oleh Family Support - Rahmaniati; Nia Ramadani; Nurbaity; Kartin Aprianti (Haka Vyza Media, 2026)
This study aims to identify the level of determinants of invisible barriers and women's career development and examine women's career development strategies. The sample in this study was 300 women in pink collar jobs. This research uses a quantitative design with data collection techniques through online and offline surveys and desk studies. The analysis uses SEM Partial least Square to analyze the 12 proposed hypotheses. The results of the study indicate that individual-level barriers, organizational-level barriers, social & cultural barriers become invisible barriers to Women’s Skill Development, and women's career development even in the pink collar jobs sector, and Family Support is a strengthening factor for women when working. The results of this study are recommendations that open opportunities for women in pink collar jobs to actively empower themselves, especially in pink collar jobs, so they can obtain equality and the same career development opportunities as men